Hisn-ul-Muslim ((3pMUpf GdeSde(B)s (Daru-l-islam Karachi, 2016)
Hisn-ul-Muslim ((3pMUpf GdeSde(B) is a comprehensive collection of authentic prayers and supplications from the Quran and Hadith, offering spiritual guidance and protection in daily life.s